Research on the selection of rotation stopping block’s arrangement for single-type low-floor tram - XIE Yuchen; LIANG Shulin; CHI Maoru; CAI Wubin; WANG Huansheng; FAN Qingyu (机车电传动)
Single-type low-floor trams have been widely used in the construction of urban light rail transit in recent years. As a common component of low-floor trams, the rotation stopping block can limit the relative swing angle range between the car body and the bogie. Its design scheme has a great impact on the movement attitude and dynamic performance of the vehicle when it passes through the small radius curve line. Determining the arrangement of the rotation stopping block on the bogie is the basis for the design of its structure and mechanical properties. At present, there are few studies on the rotation stopping block. The arrangements of the rotation stopping block and its influence have not been paid attention to. In this paper, for single-type low-floor vehicles with different arrangements of rotation stopping block, an optimization method for the rotation stopping block gap was proposed, which comprehensively considered the requirements of vehicle’s gauge and dynamic performance. The influence of different rotation stopping block arrangements on vehicle dynamic performance was studied. A design was proposed which could make the dynamic performance of the vehicle better under the condition of ensuring the same results of the vehicle gauge check. The research results show that when the vehicle passes through the small radius S-shaped curve line, with the reduction of the rotation stopping block gap, it is easier for the vehicle to meet the gauge requirements, but the curve passing safety become worse; With the premise of design conditions permitting, comprehensively considering the requirements of the vehicle’s gauge and dynamic performance, the lateral arrangement of the rotating stops is more suitable for single-type low-floor trams; If the rotation stops need to be arranged longitudinally due to the design conditions, the secondary lateral stop can be adjusted and optimized to obtain an optimized design scheme for the vehicle with better dynamic performance.